Геохимические особенности углей Кузбасса; Проблемы геологии Сибири; Т. 2 - Рихванов Л. П. Леонид Петрович; Поцелуев А. А. Анатолий Алексеевич; Ершов В. В. Василий Владимирович; Арбузов С. И. Сергей Иванович (1994, 1994)
В фонде НТБ ТПУ отсутствует